WAYS TO DEVELOP BANKING ECOSYSTEMS IN BANKS OF UZBEKISTAN - Shamshiyev Sardor Zokir ugli (Scholar Express Journals, 2025)
This article analyzes the theoretical and methodological aspects of implementing banking ecosystems in the national banking and financial sectors of the Republic of Uzbekistan, and also considers the development of digital technologies in banking. At the same time, proposals are presented for improving banking ecosystems through the development of digital technologies in the banking business
Keywords: Bank; commercial banks; digital economy; financial technology